Ongoing River Capture in the Amazon. Issue 11 (13th June 2018) - Stokes, Maya F.; Goldberg, Samuel L.; Perron, J. Taylor
Abstract: River capture is thought to trigger abrupt changes in evolving continental drainage systems, but it is almost always inferred rather than observed, and the mechanisms that lead to capture are unclear. We shed light on these mechanisms by documenting an ongoing capture involving major South American rivers. The Rio Casiquiare is a distributary of the Rio Orinoco and a tributary of the Rio Negro; it forms a perennial water connection between the drainage basins of the Amazon and Orinoco, the largest and fourth‐largest rivers on Earth by discharge. This unusual configuration is the result of an incomplete and ongoing river capture, in which the Rio Negro is capturing the upper Rio Orinoco. We describe a positive feedback between diversion of water into the capturing channel and sedimentation within the channel being captured, a mechanism that could drive river capture in the Amazon and elsewhere. Plain Language Summary: Thousands of kilometers from its outlet, the Rio Orinoco splits, sending approximately one quarter of its flow to the Rio Negro, a tributary of the Amazon River, through a channel called the Rio Casiquiare. A perennial water connection between two river basins of this size (the Amazon and Orinoco) has astonished scientists ranging from Alexander von Humboldt in the early nineteenth century to the U.S. Army Corps of Engineers during World War II. Such splits, or bifurcations, can be temporary features, suggesting that the flow that is currently divided between the Rio Orinoco and the Rio Casiquiare may eventually only flow through one of these two channels. We use measurements from a 1943 Army Corps report to analyze how water and sediment are routed through the bifurcation and present evidence that the Rio Casiquiare will eventually become the dominant channel. When this occurs, the Amazon, the largest river in the world, will have stolen 40, 000 km 2 of drainage area from the fourth‐largest Rio Orinoco. This transfer of drainage area, often called a river capture, is a rarely observed process that may influence biodiversity. We also highlight past captures that show a trend of northward expansion of the Amazon River basin. Key Points: The Rio Casiquiare diverts flow from the Orinoco river basin into the Amazon River basin Hydraulic calculations suggest that sediment deposition and erosion will lead the Rio Casiquiare to capture the Rio Orinoco headwaters The ongoing capture of the Rio Orinoco is the most recent step in an extensive reorganization of South American river systems